Analisis Break Even Point Dan Risiko Usaha Pembesaran Ikan Nila (Oreochromis niloticus) dalam Keramba Jaring Apung (KJA) di Desa Pulau Terap Kecamatan Kuok Kabupaten Kampar Provinsi Riau - Ratna Dwi Wahyuni; Eni Yulinda; Lamun Bathara (JURNAL SOSIAL EKONOMI PESISIR, 2020)
Research on Break Even Analysis Point and Business Risk of Enlargement of Tilapia (Oreochromis Niloticus) in Floating Net Cages carried out in November 2018 in Pulau Terap Village, Kuok District, Kampar District, Riau Province. This study aims to Analyze Break Even Point, Analyze the magnitude of business risk and the sources of risk found in the business of raising tilapia in the KJA business. The method used is the survey method with a total of 22 respondents. From the results of the study it was found that the BEP Q value for each cycle was 8088.9 kg, and BEP was IDR. 3793,512 / kg. Thus, the business of enlarging tilapia cultivation is feasible, because the value of BEP Q and BEP value is IDR Smaller than that at the research site. Based on the calculation, the variation coefficient value and lower profit limit value can be seen that the variation coefficient value <0.5 and the lower limit value of the profit are worth (> 0). This shows that the business will experience the benefits to be received by fish farmers in carrying out efforts to enlarge Tilapia in Floating Net Cages. Based on the results of the business analysis carried out there are sources of production risk identified in this Tilapia enlargement business. The sources of production risk are seed quality and supply, mortality, feed quality, disease, weather, and human resources.